(untitled) (FAVE Sección Ciencias Veterinarias, 2021)
A cross-sectional study was carried out in 130 freshmen at the School of Veterinary Science, Litoral National University to describe the motivations for studying veterinary medicine and their perceptions about the risk of suffering occupational diseases or occupational accidents. Statistical analysis included χ2 and Spearman’s correlation coefficient. Motivations were high for medical sciences, bovines, canines, felines and wildlife. Males showed preference for bovines (P = 0.005), while females preferred canines and felines (P˂ 0.001). Interests in agricultural activity and open spaces were not significantly associated (P= 0.598). The former was related to cattle (P˂ 0.001), sheep (P= 0.003) and pigs (P= 0.050), while the latter only to wildlife (P˂ 0.053). The most mentioned zoonosis were rabies, tuberculosis and brucellosis. The perception of the risk of zoonotic diseases was higher in pigs and cattle, while that of lesions was higher in horses. The “Don’t know / No response” answers were frequent in the recognition of some zoonoses and the perceptions of the risks of accidents and diseases. These results stress the need for early contact of veterinary students with issues related to occupational health.